Expenditure Control by Optimization of Leftover Food in The Holiday Inn Hotel Kemayoran - Ningrat, Achmad Raihan Suryadi (UI Scholars Hub, 2024)
The growth of tourism in Indonesia has positively impacted the hospitality sector, particularly in the kitchen department which is in charge of providing food and beverages to guests. Kitchen Hotel Holiday Inn Kemayoran wants to optimize the use of food scraps to control expenses without compromising food quality and hygiene. The results showed that there was a waste of food ingredients at the butcher and commissary in the hotel's main kitchen, such as chicken bones, shrimp shells, and vegetable ingredients. However, the leftovers can be processed with creative use into new dishes that reduce waste. This study provides theoretical benefits as a reference in utilizing leftover food ingredients in the Holiday Inn Kemayoran hotel kitchen, as well as practical benefits in reducing expenses and increasing hotel spending control. By managing food waste effectively, Hotel Holiday Inn Kemayoran can achieve better expense control, maintain operational sustainability, and reduce the negative impact on the environment.